Experimental study on the guiding effect of tectonic coal for coal and gas outburst. (1st February 2022) - Tu, Qingyi; Xue, Sheng; Cheng, Yuanping; Zhang, Wei; Shi, Gaofeng; Zhang, Guisheng
Highlights: The outburst development sequence is changed due to the tectonic coal area. The outburst firstly develops in the tectonic coal area. Sufficient energy is supplied to transport the coal mass to a farther distance. Abstract: The guiding effect of tectonic coal on outburst was analyzed by combining typical outburst cases, and the physical simulation experiment was carried out to reproduce the influences of tectonic coal area on the outburst. Then, the guiding action mechanism of tectonic coal on the outburst was investigated. This study concludes that the threshold value of critical gas pressure for outburst in the group with local existence of tectonic coal area was lower than that in the group without local existence of tectonic coal area. Under the gas pressure of 0.30 MPa in the group with local existence of tectonic coal area, the outburst hole was located inside the tectonic coal area, a part of pulverized coal was not thrown out yet, and the coal pillar experienced failure only nearby the outburst mouth. As the gas pressure increases, the failure degree of the coal pillar become higher and higher until complete failure. Based the experimental results, the outburst development sequence was changed due to the existence of the tectonic coal area. Once the sealing conditions were destructed, the outburst firstly develops in the tectonic coal area. Nevertheless, a large quantity of outburst energy would be suddenly released in the outburst process of the tectonic coal area, so sufficient energy was supplied to transport the coal in the tectonic coal area to a farther distance, while the residual outburst energy can just result in the outburst of a small quantity of coal masses in the normal area. This research will be of great scientific significance for explaining the tectonic coal-induced change of outburst starting and development sequence.